Molecular Imprinted Based Quartz Crystal Microbalance Sensors for Bacteria and Spores - Usman Latif; Serpil Can; Hermann F. Sussitz; Franz L. Dickert (Chemosensors, 2020)
A molecular imprinting strategy was combined with mass-sensitive transducers to generate robust and reliable biomimetic sensor systems for the detection of bioparticles. The patterning of polymers with bioanalytes enabled us to detect Escherichia coli (E. coli) bacteria with quartz crystal microbalance (QCM). The QCM sensor results were compared with direct Atomic Force Microscopy (AFM) measurements—bacteria cells adhering to the sensor coatings were counted. The recognition sites generated by Bacillus subtilis (B. subtilis) spores could successfully and reversibly recognize the template analyte and ensured rapid sensing. Cross sensitive measurements clearly showed the advantage of the molecular imprinting strategy, by which spores of Bacillus species (subtilis and thuringiensis) could easily be differentiated and selectively detected. The growth of B. subtilis from its spores was observed at 42 °C in appropriate nutrient solution of glucose and ammonium sulfate over a period of 15 h. Moreover, the growth of B. subtilis bacteria from its respective spores was studied by increasing the glucose concentration until saturation effect of the sensor. The polymeric sensor coatings were patterned to fix the B. subtilis in order to investigate osmotic effects according to a frequency response of 400 Hz by altering the ionic strength of 0.1 M.